VD_FINDINFO Décision / 2013 / 187 vom 20. Dezember 2012 - VD Tribunal cantonal (2012)
VOIES DE FAIT, ILLICÉITÉ, CLASSEMENT DE LA PROCÉDURE, POLICE, PROPORTIONNALITÉ | 123 CP, 126 CP, 14 CP, 319 CPP (CH)